Crosslinking transfer RNA and messenger RNA at the ribosomal decoding region: identification of the site of reaction on the messenger RNA. - Steiner, G (1984)
Wybutine (Ywye), situated next to the 3'-side of the anticodon of tRNAPhe from Saccharomyces cerevisiae, can be photo-crosslinked to mRNA when bound to Escherichia coli ribosomes. Crosslinking can be obtained with poly(U) as well as with oligonucleotides such as pAUGUUU or p(U)6. In order to identify the site of reaction on the mRNA, 5'-[32P]-labelled pAUGUUU was crosslinked by irradiation at 320 nm with Phe-tRNAPhe from yeast bound to the acceptor-site. The photoproduct was subsequently digested with P1-nuclease and analyzed by electrophoresis followed by homochromatography in the second dimension. As a result of the photoreaction the wybutine was found to be crosslinked to the U at the 5'-position of the corresponding UUU-codon.